PENILAIAN TINGKAT KESEHATAN KOPERASI TA’AWUN AL-IRSYAD CILACAP KETIKA DAN SETELAH PANDEMI COVID-19 - Muchlisin Muchlisin; Gading Satrio Pinandito; Veri Apriliyanto; Adi Wiratno (Jurnal Riset Akuntansi Soedirman (JRAS), 2023)
The health of cooperatives is an important aspect in maintaining the sustainability of cooperative operations and performance in facing the economic challenges caused by this pandemic. The research method used is a quantitative approach by collecting data through analysis of cooperative financial reports for the period 2020 - 2021. The data obtained is analyzed descriptively to obtain a comprehensive picture of the condition of cooperatives during and after the Covid-19 pandemic. The results of the study show that the Ta'awun Al-Irsyad Cooperative experienced changes in its level of health during and after the Covid-19 pandemic. During the pandemic, cooperatives faced major challenges, including declining revenues, operational limitations and changes in consumer behavior. This has an impact on decreasing cooperative profits and threatens the sustainability of its business. However, after the Covid-19 pandemic, the Ta'awun Al-Irsyad Cooperative was able to adapt to changing situations and take strategic steps to restore its financial health. Cooperatives increase product and service innovation, carry out financial restructuring, and strengthen cooperation with members and business partners. This effort has succeeded in increasing the performance of cooperatives and gradually restoring their level of health. This study concluded that the Covid-19 pandemic had a positive impact on the health level of the Ta'awun Al-Irsyad Cooperative in Cilacap. However, through adaptation and innovation strategies, the cooperative was able to overcome these challenges and recover gradually. This research is expected to contribute to understanding the role of cooperatives in facing the economic crisis and provide insight for other cooperatives in facing similar situations in the future.